Proving foldr f st (xs++ys) = f (foldr f st xs) (foldr f st ys) - haskell

I am trying to prove the following statement by structural induction:
foldr f st (xs++yx) = f (foldr f st xs) (foldr f st ys) (foldr.3)
However I am not even sure how to define foldr, so I am stuck as no definitions have been provided to me. I now believe that foldr can be defined as
foldr f st [] = st (foldr.1)
foldr f st x:xs = f x (foldr f st xs) (foldr.2)
Now I want to start working on the base case passing the empty list to foldr. I have this, but I don't think it is correct.
foldr f st ([]++[]) = f (foldr f st []) (foldr f st [])
LHS:
foldr f st ([]++[]) = foldr f st [] by (++)
foldr f st [] = st by (foldr.1)
RHS:
f (foldr f st []) (foldr f st []) = f st st by (foldr.1)
= st by definition of identity, st = 0
LHS = RHS, therefore base case holds
Now this is what I have for my inductive step:
Assume that:
foldr f st (xs ++ ys) = f (foldr f st xs) (foldr f st ys) (ind. hyp)
Show that:
foldr f st (x:xs ++ ys) = f (foldr f st x:xs) (foldr f st ys) (inductive step)
LHS:
foldr f st (x:xs ++ ys) = f x (foldr f st xs) (foldr f st ys) (by foldr.2)
RHS:
f (foldr f st x:xs) (foldr f st ys) =
= f f x (foldr f st xs) (foldr f st ys) (by foldr.2)
= f x (foldr f st xs) (foldr f st ys)
LHS = RHS, therefore inductive step holds. End of proof.
I am not sure if this proof is valid. I need some help in determining if it correct and if not - what part of it is not.

First: you can find the definition for many basic Haskell functions via the API documentation, which is available on Hackage. The documentation for base is here. foldr is exported in Prelude, which has a link to its source code:
foldr :: (a -> b -> b) -> b -> [a] -> b
foldr k z = go
where
go [] = z
go (y:ys) = y `k` go ys
It's defined like this for efficiency reasons; look up "worker-wrapper." It's equivalent to
foldr f st [] = st
foldr f st (y:ys) = f y (foldr f st ys)
Second: In your desired proof, the type of f must be a -> a -> a, which is less general than a -> b -> b.
Let's work through the base case (xs = ys = []).
foldr f st ([]++[]) = f (foldr f st []) (foldr f st [])
-- Definition of ++
foldr f st [] = f (foldr f st []) (foldr f st [])
-- Equation 1 of foldr
st = f st st
This equation does not hold in general. To proceed with the proof, you'll have to assume that st is an identity for f.
You'll also have to assume, in the non-base case, that f is associative, I believe. These two assumptions, combined, indicate that f and st form a monoid. Are you trying to prove something about foldMap?

Related

How can two continuations cancel each other out?

I'm reading through Some Tricks for List Manipulation, and it contains the following:
zipRev xs ys = foldr f id xs snd (ys,[])
where
f x k c = k (\((y:ys),r) -> c (ys,(x,y):r))
What we can see here is that we have two continuations stacked on top
of each other. When this happens, they can often “cancel out”, like
so:
zipRev xs ys = snd (foldr f (ys,[]) xs)
where
f x (y:ys,r) = (ys,(x,y):r)
I don't understand how you "cancel out" stacked continuations to get from the top code block to the bottom one. What pattern do you look for to make this transformation, and why does it work?
A function f :: a -> b can be "disguised" inside double continuations as a function f' :: ((a -> r1) -> r2) -> ((b -> r1) -> r2).
obfuscate :: (a -> b) -> ((a -> r1) -> r2) -> (b -> r1) -> r2
obfuscate f k2 k1 = k2 (k1 . f)
obfuscate has the nice property that it preserves function composition and identity: you can prove that obfuscate f . obfuscate g === obfuscate (f . g) and that obfuscate id === id in a few steps. That means that you can frequently use this transformation to untangle double-continuation computations that compose obfuscated functions together by factoring the obfuscate out of the composition. This question is an example of such an untangling.
The f in the top code block is the obfuscated version of the f in the bottom block (more precisely, top f x is the obfuscated version of bottom f x). You can see this by noticing how top f applies the outer continuation to a function that transforms its input and then applies the whole thing to the inner continuation, just like in the body of obfuscate.
So we can start to untangle zipRev:
zipRev xs ys = foldr f id xs snd (ys,[])
where
f x = obfuscate (\(y:ys,r) -> (ys,(x,y):r))
Since the action of foldr here is to compose a bunch of obfuscated functions with each other (and apply it all to id, which we can leave on the right), we can factor the obfuscate to the outside of the whole fold:
zipRev xs ys = obfuscate (\accum -> foldr f accum xs) id snd (ys,[])
where
f x (y:ys,r) = (ys,(x,y):r)
Now apply the definition of obfuscate and simplify:
zipRev xs ys = obfuscate (\accum -> foldr f accum xs) id snd (ys,[])
zipRev xs ys = id (snd . (\accum -> foldr f accum xs)) (ys,[])
zipRev xs ys = snd (foldr f (ys,[]) xs)
QED!
Given a function
g :: a₁ -> a₂
we can lift it to a function on continuations, switching the order:
lift g = (\c a₁ -> c (g a₁))
:: (a₂ -> t) -> a₁ -> t
This transformation is a contravariant functor, which is to say that it interacts with function composition by switching its order:
g₁ :: a₁ -> a₂
g₂ :: a₂ -> a₃
lift g₁ . lift g₂
== (\c₁ a₁ -> c₁ (g₁ a₁)) . (\c₂ a₂ -> c₂ (g₂ a₂))
== \c₂ a₁ -> (\a₂ -> c₂ (g₂ a₂)) (g₁ a₁)
== \c₂ a₁ -> c₂ (g₂ (g₁ a₁))
== lift (g₂ . g₁)
:: (a₃ -> t) -> a₁ -> t
lift id
== (\c a₁ -> c a₁)
== id
:: (a₁ -> t) -> a₁ -> t
We can lift the lifted function again in the same way to a function on stacked continuations, with the order switched back:
lift (lift g)
== (\k c -> k ((\c a₁ -> c (g a₁)) c))
== (\k c -> k (\a₁ -> c (g a₁)))
:: ((a₁ -> t) -> u) -> (a₂ -> t) -> u
Stacking two contravariant functors gives us a (covariant) functor:
lift (lift g₁) . lift (lift g₂)
== lift (lift g₂ . lift g₁)
== lift (lift (g₁ . g₂))
:: ((a₁ -> t) -> u) -> (a₃ -> t) -> u
lift (lift id)
== lift id
== id
:: ((a₁ -> t) -> u) -> (a₁ -> t) -> u
This is exactly the transformation being reversed in your example, with g = \(y:ys, r) -> (ys, (x, y):r). This g is an endomorphism (a₁ = a₂), and the foldr is composing together a bunch of copies of it with various x. What we’re doing is replacing the composition of double-lifted functions with the double-lift of the composition of the functions, which is just an inductive application of the functor laws:
f :: x -> a₁ -> a₁
c :: (a₁ -> t) -> u
xs :: [x]
foldr (\x -> lift (lift (f x))) c xs
== lift (lift (\a₁ -> foldr f a₁ xs)) c
:: (a₁ -> t) -> u
Let's try to understand this code from an elementary point of view. What does it even do, one wonders?
zipRev xs ys = foldr f id xs snd (ys,[])
where
-- f x k c = k (\(y:ys, r) -> c (ys, (x,y):r))
f x k c = k (g x c)
-- = (k . g x) c -- so,
-- f x k = k . g x
g x c (y:ys, r) = c (ys, (x,y):r)
Here we used lambda lifting to recover the g combinator.
So then because f x k = k . g x were k goes to the left of x, the input list is translated into a reversed chain of compositions,
foldr f id [x1, x2, x3, ..., xn] where f x k = k . g x
===>>
(((...(id . g xn) . ... . g x3) . g x2) . g x1)
and thus, it just does what a left fold would do,
zipRev [] ys = []
zipRev [x1, x2, x3, ..., xn] ys
= (id . g xn . ... . g x3 . g x2 . g x1) snd (ys, [])
= g xn (g xn1 ( ... ( g x3 ( g x2 ( g x1 snd)))...)) (ys, [])
where ----c--------------------------------------------
g x c (y:ys, r) = c (ys, (x,y):r)
So we went to the deep end of the xs list, and then we come back consuming the ys list left-to-right (i.e. top-down) on our way back right-to-left on the xs list (i.e. bottom-up). This is straightforwardly coded as a right fold with strict reducer, so the flow is indeed right-to-left on the xs. The bottom-most action (snd) in the chain is done last, so in the new code it becomes the topmost (still done last):
zipRev xs ys = snd (foldr h (ys,[]) xs)
where
h x (y:ys, r) = (ys, (x,y):r)
g x c was used as a continuation in the original code, with c as a second-tier continuation; but it's actually all just been a regular fold from the right, all along.
So indeed it zips the reversed first list with the second. It's also unsafe; it misses a clause:
g x c ([], r) = c ([], r) -- or just `r`
g x c (y:ys, r) = c (ys, (x,y):r)
(update:) The answers by duplode (and Joseph Sible) do the lambda lifting a bit differently, in a way which is better suited to the task. It goes like this:
zipRev xs ys = foldr f id xs snd (ys,[])
where
f x k c = k (\((y:ys), r) -> c (ys, (x,y):r))
= k (c . (\((y:ys), r) -> (ys, (x,y):r)) )
= k (c . g x)
g x = (\((y:ys), r) -> (ys, (x,y):r))
{- f x k c = k ((. g x) c) = (k . (. g x)) c = (. (. g x)) k c
f x = (. (. g x)) -}
so then
foldr f id [ x1, x2, ... , xn ] snd (ys,[]) =
= ( (. (. g x1)) $ (. (. g x2)) $ ... $ (. (. g xn)) id ) snd (ys,[]) -- 1,2...n
= ( id . (. g xn) . ... . (. g x2) . (. g x1) ) snd (ys,[]) -- n...2,1
= ( snd . g x1 . g x2 . ... . g xn ) (ys,[]) -- 1,2...n!
= snd $ g x1 $ g x2 $ ... $ g xn (ys,[])
= snd $ foldr g (ys,[]) [x1, x2, ..., xn ]
Simple. :) Flipping twice is no flipping at all.
Let's begin with a few cosmetic adjustments:
-- Note that `g x` is an endomorphism.
g :: a -> ([b], [(a,b)]) -> ([b], [(a,b)])
g x ((y:ys),r) = (ys,(x,y):r)
zipRev xs ys = foldr f id xs snd (ys,[])
where
f x k = \c -> k (c . g x)
f feeds a continuation (c . g x) to another function (k, a "double continuation", as user11228628 puts it).
While we might reasonably expect that repeated usage of f as the fold proceeds will somehow compose the g x endomorphisms made out of the elements of the list, the order in which the endomorphisms are composed might not be immediately obvious, so we'd better walk through a few fold steps to be sure:
-- x0 is the first element, x1 the second, etc.
f x0 k0
\c -> k0 (c . g x0)
\c -> (f x1 k1) (c . g x0) -- k0 is the result of a fold step.
\c -> (\d -> k1 (d . g x1)) (c . g x0) -- Renaming a variable for clarity.
\c -> k1 (c . g x0 . g x1)
-- etc .
-- xa is the *last* element, xb the next-to-last, etc.
-- ka is the initial value passed to foldr.
\c -> (f xa ka) (c . g x0 . g x1 . . . g xb)
\c -> (\d -> ka (d . g xa)) (c . g x0 . g x1 . . . g xb)
\c -> ka (c . g x0 . g x1 . . . g xb . g xa)
ka, the initial value passed to foldr, is id, which makes things quite a bit simpler:
foldr f id xs = \c -> c . g x0 . g x1 . . . g xa
Since all we do with the c argument passed to foldr f id xs is post-composing it with the endomorphisms, we might as well factor it out of the fold:
zipRev xs ys = (snd . foldr h id xs) (ys,[])
where
h x e = g x . e
Note how we have gone from c . g x to g x . e. That can arguably be described as a collateral effect of the CPS trickery in the original implementation.
The final step is noticing how h x e = g x . e corresponds exactly to what we would do to implement foldr in terms of foldMap for the Endo monoid. Or, to put it more explicitly:
foldEndo g i xs = foldr g i xs -- The goal is obtaining an Endo-like definition.
foldEndo _ i [] = i
foldEndo g i (x : xs) = g x (foldEndo g i xs)
foldEndo g i xs = go xs i
where
go [] = \j -> j
go (x : xs) = \j -> g x (foldEndo g j xs)
foldEndo g i xs = go xs i
where
go [] = \j -> j
go (x : xs) = \j -> g x (go xs j)
foldEndo g i xs = go xs i
where
go [] = id
go (x : xs) = g x . go xs
foldEndo g i xs = go xs i
where
h x e = g x . e
go [] = id
go (x : xs) = h x (go xs)
foldEndo g i xs = go xs i
where
h x e = g x . e
go xs = foldr h id xs
foldEndo g i xs = foldr h id xs i
where
h x e = g x . e
That finally leads us to what we were looking for:
zipRev xs ys = snd (foldr g (ys,[]) xs)
user11228628's answer led me to understanding. Here's a few insights I had while reading it, and some step-by-step transformations.
Insights
The continuations don't directly cancel out. They can only eventually be canceled (by beta-reducing) because it's possible to factor them out.
The pattern you're looking for to do this transformation is \k c -> k (c . f) (or if you love unreadable pointfree, (. (. f))) for any f (note that the f isn't a parameter to the lambda).
As duplode points out in a comment, continuation-passing style functions can be considered a functor, and obfuscate is their definition of fmap.
The trick of pulling a function like this out of foldr works for any function that could be a valid fmap.
Full transformation from the first code block to the second
zipRev xs ys = foldr f id xs snd (ys,[])
where
f x k c = k (\((y:ys),r) -> c (ys,(x,y):r))
Pull c out of the lambda
zipRev xs ys = foldr f id xs snd (ys,[])
where
f x k c = k (c . \((y:ys),r) -> (ys,(x,y):r))
Substitute obfuscate for its definition
zipRev xs ys = foldr f id xs snd (ys,[])
where
f x = obfuscate (\((y:ys),r) -> (ys,(x,y):r))
Pull obfuscate out of the lambda
zipRev xs ys = foldr f id xs snd (ys,[])
where
f = obfuscate . \x ((y:ys),r) -> (ys,(x,y):r)
Pull obfuscate out of f
zipRev xs ys = foldr (obfuscate . f) id xs snd (ys,[])
where
f x ((y:ys),r) = (ys,(x,y):r)
Since obfuscate follows the Functor laws, we can pull it out of foldr
zipRev xs ys = obfuscate (flip (foldr f) xs) id snd (ys,[])
where
f x ((y:ys),r) = (ys,(x,y):r)
Inline obfuscate
zipRev xs ys = (\k c -> k (c . flip (foldr f) xs)) id snd (ys,[])
where
f x ((y:ys),r) = (ys,(x,y):r)
Beta-reduce
zipRev xs ys = (id (snd . flip (foldr f) xs)) (ys,[])
where
f x ((y:ys),r) = (ys,(x,y):r)
Simplify
zipRev xs ys = snd (foldr f (ys,[]) xs)
where
f x (y:ys,r) = (ys,(x,y):r)
Justification for pulling functions that are valid fmaps out of foldr
foldr (fmap . f) z [x1,x2,...,xn]
Expand the foldr
(fmap . f) x1 . (fmap . f) x2 . ... . (fmap . f) xn $ z
Inline the inner .s
fmap (f x1) . fmap (f x2) . ... . fmap (f xn) $ z
Apply the Functor laws
fmap (f x1 . f x2 . ... . f xn) $ z
Eta-expand the section in parentheses
fmap (\z2 -> f x1 . f x2 . ... . f xn $ z2) z
Write the lambda body in terms of foldr
fmap (\z2 -> foldr f z2 [x1,x2,...,xn]) z
Write the lambda body in terms of flip
fmap (flip (foldr f) [x1,x2,...,xn]) z
Bonus: Justification for pulling functions that are valid contramaps out of foldr
foldr (contramap . f) z [x1,x2,...,xn]
Expand the foldr
(contramap . f) x1 . (contramap . f) x2 . ... . (contramap . f) xn $ z
Inline the inner .s
contramap (f x1) . contramap (f x2) . ... . contramap (f xn) $ z
Apply the Contravariant laws
contramap (f xn . ... . f x2 . f x1) $ z
Eta-expand the section in parentheses
contramap (\z2 -> f xn . ... . f x2 . f x1 $ z2) z
Write the lambda body in terms of foldr
contramap (\z2 -> foldr f z2 [xn,...,x2,x1]) z
Write the lambda body in terms of flip
contramap (flip (foldr f) [xn,...,x2,x1]) z
Apply foldr f z (reverse xs) = foldl (flip f) z xs
contramap (flip (foldl (flip f)) [x1,x2,...,xn]) z

Using foldr to define map (develop)

Having a hard time understanding fold... Is the expansion correct ? Also would appreciate any links, or analogies that would make fold more digestible.
foldMap :: (a -> b) -> [a] -> [b]
foldMap f [] = []
foldMap f xs = foldr (\x ys -> (f x) : ys) [] xs
b = (\x ys -> (f x):ys)
foldMap (*2) [1,2,3]
= b 1 (b 2 (foldr b [] 3))
= b 1 (b 2 (b 3 ( b [] [])))
= b 1 (b 2 ((*2 3) : []))
= b 1 ((*2 2) : (6 :[]))
= (* 2 1) : (4 : (6 : []))
= 2 : (4 : (6 : []))
First, let's not use the name foldMap since that's already a standard function different from map. If you want to re-implement an existing function with the same or similar semantics, convention is to give it the same name but either in a separate module, or with a prime ' appended to the name. Also, we can omit the empty-list case, since you can just pass that to the fold just as well:
map' :: (a -> b) -> [a] -> [b]
map' f xs = foldr (\x ys -> f x : ys) [] xs
Now if you want to evaluate this function by hand, first just use the definition without inserting anything more:
map' (*2) [1,2,3,4]
≡ let f = (*2)
xs = [1,2,3,4]
in foldr (\x ys -> (f x) : ys) [] xs
≡ foldr (\x ys -> (*2) x : ys) [] [1,2,3,4]
Now just prettify a bit:
≡ foldr (\x ys -> x*2 : ys) [] [1,2,3,4]
Now to evaluate this through, you also need the definition of foldr. It's actually a bit different in GHC, but effectively
foldr _ z [] = z
foldr f z (x:xs) = f x (foldr f z xs)
So with your example
...
≡ foldr (\x ys -> x*2 : ys) [] (1:[2,3,4])
≡ (\x ys -> x*2 : ys) 1 (foldr (\x ys -> x*2 : ys) [] [2,3,4])
Now we can perform a β-reduction:
≡ 1*2 : foldr (\x ys -> x*2 : ys) [] [2,3,4]
≡ 2 : foldr (\x ys -> x*2 : ys) [] [2,3,4]
...and repeat for the recursion.
foldr defines a family of equations,
foldr g n [] = n
foldr g n [x] = g x (foldr g n []) = g x n
foldr g n [x,y] = g x (foldr g n [y]) = g x (g y n)
foldr g n [x,y,z] = g x (foldr g n [y,z]) = g x (g y (g z n))
----- r ---------
and so on. g is a reducer function,
g x r = ....
accepting as x an element of the input list, and as r the result of recursively processing the rest of the input list (as can be seen in the equations).
map, on the other hand, defines a family of equations
map f [] = []
map f [x] = [f x] = (:) (f x) [] = ((:) . f) x []
map f [x,y] = [f x, f y] = ((:) . f) x (((:) . f) y [])
map f [x,y,z] = [f x, f y, f z] = ((:) . f) x (((:) . f) y (((:) . f) z []))
= (:) (f x) ( (:) (f y) ( (:) (f z) []))
The two families simply exactly match with
g = ((:) . f) = (\x -> (:) (f x)) = (\x r -> f x : r)
and n = [], and thus
foldr ((:) . f) [] xs == map f xs
We can prove this rigorously by mathematical induction on the input list's length, following the defining laws of foldr,
foldr g n [] = []
foldr g n (x:xs) = g x (foldr g n xs)
which are the basis for the equations at the top of this post.
Modern Haskell has Fodable type class with its basic fold following the laws of
fold(<>,n) [] = n
fold(<>,n) (xs ++ ys) = fold(<>,n) xs <> fold(<>,n) ys
and the map is naturally defined in its terms as
map f xs = foldMap (\x -> [f x]) xs
turning [x, y, z, ...] into [f x] ++ [f y] ++ [f z] ++ ..., since for lists (<>) == (++). This follows from the equivalence
f x : ys == [f x] ++ ys
This also lets us define filter along the same lines easily, as
filter p xs = foldMap (\x -> [x | p x]) xs
To your specific question, the expansion is correct, except that (*2 x) should be written as ((*2) x), which is the same as (x * 2). (* 2 x) is not a valid Haskell (though valid Lisp :) ).
Functions like (*2) are known as "operator sections" -- the missing argument goes into the empty slot: (* 2) 3 = (3 * 2) = (3 *) 2 = (*) 3 2.
You also asked for some links: see e.g. this, this and this.

Recursive definitions of scanl and scanr in Haskell

I have searched but cannot find simple definitions of the functions scanr and scanl, only explanations that they show the intermediate calculations of the functions foldr and foldl (respectively).
I have written a recursive definition for scanl, based on the foldl property foldl f y (x:xs) = foldl f (f y x) xs:
scanl' :: (b -> a -> b) -> b -> [a] -> [b]
scanl' f x [] = [x]
scanl' f x (y:ys) = x : scanl' f (f x y) ys
This seems to work. However, there is a type error when I try to apply this analogy with the foldr property foldr f y (x:xs) = f x (foldr f y xs):
scanr' :: (a -> b -> b) -> b -> [a] -> [b]
scanr' _ x [] = [x]
scanr' f x (y:ys) = y : f x (scanr' f x ys)
This fails as the second input for f needs to be a b not a [b]. However, I am unsure how to do this while also recursing on scanr'.
To compute
result = scanr' f x (y:ys)
you must have computed
partialResult = scanr' f x ys
after which you get
result = (y `f` head partialResult) : partialResult
The complete implementation is
scanr' _ x [] = [x]
scanr' f x (y:ys) = (y `f` head partialResult) : partialResult
where partialResult = scanr' f x ys
scanl1 (\acc x -> if x > acc then x else acc)[3,4,5,3,7,9,2,1]
from Learn You A Haskell seems to have only two arguments: the function and the list. Yet it works. It even works if you write it as:
scanl1 (\x acc -> if x > acc then x else acc)[3,4,5,3,7,9,2,1]
Slightly puzzling why works.

Is this proof I wrote correct and what's wrong if not?

I already asked a different question realted to this proof, so I'm sorry for duplicate. Just nobody would answer any more, because the other one has an answer.
I am trying to prove the following statement by structural induction:
foldr f st (xs++yx) = f (foldr f st xs) (foldr f st ys) (foldr.3)
These are the definitions of foldr:
foldr f st [] = st (foldr.1)
foldr f st x:xs = f x (foldr f st xs) (foldr.2)
Now I want to start working on the base case passing the empty list to xs. I have this, but I don't know if it is correct.
foldr f st ([]++ys) = f (foldr f st []) (foldr f st ys)
LHS:
foldr f st ([]++ys)
= foldr f st ys by (++) and by (foldr.1)
RHS:
f (foldr f st []) (foldr f st ys) =
= f st (foldr f st ys) by (foldr.1)
= foldr f st ys by def of st = 0 and f = (+)
LHS = RHS, therefore base case holds
Now this is what I have for my inductive step:
Assume that:
foldr f st (xs ++ ys) = f (foldr f st xs) (foldr f st ys) (ind. hyp)
Show that:
foldr f st (x:xs ++ ys) = f (foldr f st x:xs) (foldr f st ys)
LHS:
foldr f st (x:xs ++ ys)
= f x (foldr f st (xs++yx)) (by foldr.2)
= f x (f (foldr f st xs) (foldr f st ys) ) (by ind. hyp)
= f (f x (foldr f st xs)) (foldr f st ys) (by assosiativity of f)
RHS:
f (foldr f st x:xs) (foldr f st ys)
= f (f x (foldr f st xs)) (foldr f st ys) (by foldr.2)
LHS = RHS, therefore inductive step holds. End of proof.
I am not sure if this proof is valid. I need some help in determining if it correct and if not - what part of it is not.
before you start to prove something, check a few examples, e.g.,
xs = ys = [] ; st = True ; f _ _ = False
Upd: The question was edited multiple times. The following makes sense in revision 1 of the question.
This is not possible to prove. You need f to be a monoid: f a (f b c) == f (f a b) c with f a st == a and f st a == a.
A provable statement would be foldr f st (xs++ys) == foldr f (foldr f st ys) xs
Assuming f with st define a monoid, we get the following statements:
foldr f st ([]++ys) ==
-- by definition of neutral element of list monoid, []++ys == ys
== foldr f st ys
-- by definition of neutral element of `f` monoid, f st a == a
== f st (foldr f st ys)
-- by definition of foldr, (foldr f st []) == st
== f (foldr f st []) (foldr f st ys)
Then,
foldr f st ((x:xs)++ys) ==
-- by associativity of list monoid, (x:xs)++ys == x:(xs++ys)
== foldr f st (x:(xs++ys))
-- by definition of foldr, foldr f st (x:t) == f x (foldr f st t)
== f x (foldr f st (xs++ys))
-- by induction, foldr f st (xs++ys) == f (foldr f st xs) (foldr f st ys)
== f x (f (foldr f st xs) (foldr f st ys))
-- by associativity of monoid `f`, f x (f y z) == f (f x y) z
== f (f x (foldr f st xs)) (foldr f st ys)
-- by definition of foldr, f x (foldr f st t) == foldr f st (x:t)
== f (foldr f st (x:xs)) (foldr f st ys)
In essence, this is the proof of the monoid homomorphism. Lists being a free monoid, the homomorphism exists, and is exactly of the form you are seeking - it is the catamorphism for f.

Fusion law for foldr1?

For foldr we have the fusion law: if f is strict, f a = b, and
f (g x y) = h x (f y) for all x, y, then f . foldr g a = foldr h b.
How can one discover/derive a similar law for foldr1? (It clearly can't even take the same form - consider the case when both sides act on [x].)
You can use free theorems to derive statements like the fusion law. The Automatic generation of free theorems does this work for you, it automatically derives the following statement if you enter foldr1 or the type (a -> a -> a) -> [a] -> a.
If f strict and f (p x y) = q (f x) (f y)) for all x and y you have f (foldr1 p z) = foldr1 q (map f z)). That is, in contrast to you statement about foldr you get an additional map f on the right hand side.
Also note that the free theorem for foldr is slightly more general than your fusion law and, therefore, looks quite similar to the law for foldr1. Namely you have for strict functions g and f if g (p x y) = q (f x) (g y)) for all x and y then g (foldr p z v) = foldr q (g z) (map f v)).
I don't know if there's going to be anything satisfying for foldr1. [I think] It's just defined as
foldr1 f (x:xs) = foldr f x xs
let's first expand what you have above to work on the entire list,
f (foldr g x xs) = foldr h (f x) xs
for foldr1, you could say,
f (foldr1 g xs) = f (foldr g x xs)
= foldr h (f x) xs
to recondense into foldr1, you can create some imaginary function that maps f to the left element, for a result of,
f . foldr1 g = foldr1 h (mapfst f) where
mapfst (x:xs) = f x : xs

Resources